From climate risk to resilience: Unpacking the economic impacts of climate change in Kenya - Detelinova, Iva; Thomas, Timothy S.; Hammond, Wole; Arndt, Channing; Hartley, Faaiqa (International Food Policy Research Institute, 2023)
Substantial model variability exists regarding the likely meteorological impact of climate change on Kenya, particularly with respect to future precipitation levels. Significant regional differences are expected, largely due to Kenya’s diverse climate profile. Overall, temperatures are projected to increase while future precipitation levels are highly uncertain. Climate change is expected to significantly affect coastal areas, including because of sea level rise risks, stronger winds, and an overall warmer and drier climate. This will likely harm important ecosystems, including wetlands, mangroves, and coral reefs. Some models project that arid and semi-arid areas may become drier and hotter, which would exacerbate preexisting water scarcity and agricultural challenges for the already vulnerable communities living there. That said, these projections are not corroborated by all models. The climate change impact on other areas, particularly south and west of Mount Kenya, could generally be positive, as it would provide even better conditions for agriculture. The key climate change risk for Kenya is from extreme events, in particular droughts and floods. The frequency and intensity of such events is likely to increase because of climate change. They also often lead to adverse knock-on effects, such as soil erosion, land degradation, and pest breakouts. Overall, Kenya’s updated Nationally Determined Contribution (NDC) (2020) estimates that between 2010 and 2020, adverse climate change-related events led to annual socioeconomic losses of 3–5 percent of total gross domestic product (GDP).